Analysis of Stunting Phenomenon in Sragen Regency During The COVID-19 Pandemic from Economic Perspective - Sri Wulandari Setiyanto; Sri Suparti (Media Kesehatan Masyarakat Indonesia, 2022)
The COVID-19 pandemic has hit all countries in the world including Indonesia. To prevent the spread of the virus, the PSBB and PPKM policies have been implemented and these policies have crippled economic activities which have an economy impact and food security. The purpose of this study was to analyze the effect of economic and food security during the COVID-19 pandemic on toddler stunting status including 1) knowing the relation of economy on food security, 2) knowing the effect of economic and food security. on toddler stunting. This research is an observational study with a cross-sectional design. The data in this study were data on children under five years old years old, family economic status, and family food security status. The population of this study was toddlers aged 0-5 in Sragen Regency in 2020. The sampling technique is cluster sampling. Data analysis used the Spearman correlation technique and binary logistic regression. The results of the study are 1) Economic status is related to food security (r = 0.637, p-value = 0.000), 2) Economic status affects stunting of children under five years old years old (B = 1.460; p-value = 0.006; OR = 4,307), 3) Food security affects the stunting of children under five years old years old (B = 5.028; p-value = 0.000; OR=152,660). Economic and food security affect toddler stunting in Sragen Regency during the COVID-19 pandemic. The incidence of stunting is still common in Indonesia, further research can be carried out to analyze other factors that influence stunting according to the conditions of the toddler area.